Effects of trawling on sessile megabenthos in the Great Barrier Reef and evaluation of the efficacy of management strategies. (14th April 2015) - Pitcher, C. Roland; Ellis, Nick; Venables, William N.; Wassenberg, Ted J.; Burridge, Charis Y.; Smith, Greg P.; Browne, Matthew; Pantus, Francis; Poiner, Ian R.; Doherty, Peter J.; Hooper, John N.A.; Gribble, Neil
Abstract: A series of related research studies over 15 years assessed the effects of prawn trawling on sessile megabenthos in the Great Barrier Reef, to support management for sustainable use in the World Heritage Area. These large-scale studies estimated impacts on benthos (particularly removal rates per trawl pass), monitored subsequent recovery rates, measured natural dynamics of tagged megabenthos, mapped the regional distribution of seabed habitats and benthic species, and integrated these results in a dynamic modelling framework together with spatio-temporal fishery effort data and simulated management. Typical impact rates were between 5 and 25% per trawl, recovery times ranged from several years to several decades, and most sessile megabenthos were naturally distributed in areas where little or no trawling occurred and so had low exposure to trawling. The model simulated trawl impact and recovery on the mapped species distributions, and estimated the regional scale cumulative changes due to trawling as a time series of status for megabenthos species. The regional status of these taxa at time of greatest depletion ranged from ∼77% relative to pre-trawl abundance for the worst case species, having slow recovery with moderate exposure to trawling, to ∼97% for the least affected taxon. The model also evaluated the expected outcomes for sessile megabenthos in response to major management interventions implemented between 1999 and 2006, including closures, effort reductions, and protected areas. As a result of these interventions, all taxa were predicted to recover (by 2–14% at 2025); the most affected species having relatively greater recovery. Effort reductions made the biggest positive contributions to benthos status for all taxa, with closures making smaller contributions for some taxa. The results demonstrated that management actions have arrested and reversed previous unsustainable trends for all taxa assessed, and have led to a prawn trawl fishery with improved environmental sustainability.